A season long investigation into the effects of injury, match selection and training load on mental wellbeing in professional under 23 soccer players: A team case study. Issue 9 (21st October 2019) - Abbott, Will; Brownlee, Thomas E.; Harper, Liam D.; Naughton, Robert J.; Richardson, Andy; Clifford, Tom
Abstract : This study examined the influence of injury, match selection and training load on mental wellbeing (MW) in a squad of professional soccer players. Using a longitudinal design, twenty-five male soccer players (age, 20 ± 1 years, height, 1.80 ± 5.79 m, body mass 76.33 ± 7.52 kg) from the under 23 squad playing in the Premier League 2 division in the UK completed the Warwick–Edinburgh Mental Well-being Scale (WEMWBS) each week of the 2017/2018 season (37 weeks in total). Injury and non-selection for the match squad were the only significant predictors of MW ( P < 0.05). Injury had the biggest influence on MW that was lower when injured vs. not injured (43.6 ± 5.0 vs. 49.9 ± 3.5, respectively, P = 0.001, ES = 1.48), accounting for 40% of the variation in MW. This increased to 50% when not being selected to play games was also considered. Weekly training loads measured by GPS (total distance, sprint distance and total duration) and individual player win rate did not influence MW ( P > 0.05). These findings highlight the importance of monitoring MW in professional soccer players and suggest that injured players and those rarely selected for the match squad should be educated on the strategies available for managing their mental health and wellbeing.